Contraband (A Stone Barrington novel, 50,, 2019)
Stone Barrington is getting some much-needed rest and relaxation in the Florida sun when trouble falls from the sky--literally. Intrigued by the suspicious circumstances surrounding this event, Stone joins forces with a sharp-witted and alluring local detective to investigate. But they run into a problem: the evidence keeps disappearing. From the laid-back Key West shores to the bustling Manhattan streets, Stone sets out to connect the dots between the crimes that seem to follow him wherever he travels. His investigations only lead to more questions, and shocking connections between old and new acquaintances. But as Stone must quickly learn, answers--and enemies--are often hiding in plain sight.-- Provided by publisher

Missing you (Dutton, Orion Pub. Co, Penguin Group USA, 2017)
"From #1 New York Times bestselling author Harlan Coben, a heart-pounding thriller about the ties we have to our past...and the lies that bind us together. It's a profile, like all the others on the online dating site. But as NYPD Detective Kat Donovan focuses on the accompanying picture, she feels her whole world explode, as emotions she's ignored for decades come crashing down on her. Staring back at her is her ex-fiance; Jeff, the man who shattered her heart-and who she hasn't seen in 18 years. Kat feels a spark, wondering if this might be the moment when past tragedies recede and a new world opens up to her. But when she reaches out to the man in the profile, her reawakened hope quickly darkens into suspicion and then terror as an unspeakable conspiracy comes to light, in which monsters prey upon the most vulnerable. As the body count mounts and Kat's hope for a second chance with Jeff grows more and more elusive, she is consumed by an investigation that challenges her feelings about everyone she ever loved, her former fiance, her mother, and even her father, whose cruel murder so long ago has never been fully explained. With lives on the line, including her own, Kat must venture deeper into the darkness than she ever has before, and discover if she has the strength to survive what she finds there"--

The witness (Distributed by Recorded Books, G. P. Putnam's Sons, Brilliance Audio, G.P. Putnam's Sons, 2012)
Having had a traumatic experience twelve years prior, Abigail Lowery lives in a remote area in a house with high-tech security measures, but this only serves to further intrigue police chief Brooks Gleason, who aims to protect Abigail.

Fearless (Kensington Publishing, Kensington Publishing Corp, 2020)
Weaving a thread of suspense into her trademark powerful storytelling, #1 New York Times bestselling author Fern Michaels delivers a compelling new novel about a woman who learns that her new life may not be all it appears . . . Anna Campbell is ready to take her first tentative steps back into the world after widowhood. On a singles cruise, she meets divorced professor Ryan Robertson, and the sparks between them are undeniable. Back home in West Texas, Anna and Ryan continue their romance, and Anna decides it's time for their families to meet. Anna is delighted when her daughter, Christina, hits it off with Ryan's daughter, Renee. The two girls are close in age and have lots in common. Ryan's son, Patrick, is college-bound and somewhat aloof, but Anna feels sure they'll grow closer in time. She happily accepts Ryan's proposal, confident in the bond they've formed. But the idyllic relationships Anna is hoping for is quickly thrown into doubt. Ryan and his children may not be all she thinks they are. And as the situation grows more desperate, Anna must reach deep within and draw on all her courage and self-reliance to fight for the family and home she deserves . . .

Come sundown (Thorndike Press large print basic, ,, 2017)
"A novel of suspense, family ties, and twisted passions from the #1 New York Times bestselling author of The Obsession... The Bodine ranch and resort in western Montana is a family business, an idyllic spot for vacationers. A little over thirty thousand acres and home to four generations, it's kept running by Bodine Longbow with the help of a large staff, including new hire Callen Skinner. There was another member of the family once: Bodine's aunt, Alice, who ran off before Bodine was born. She never returned, and the Longbows don't talk about her much. The younger ones, who never met her, quietly presume she's dead. But she isn't. She is not far away, part of a new family, one she never chose--and her mind has been shattered... When a bartender leaves the resort late one night, and Bo and Cal discover her battered body in the snow, it's the first sign that danger lurks in the mountains that surround them. The police suspect Cal, but Bo finds herself trusting him--and turning to him as another woman is murdered and the Longbows are stunned by Alice's sudden reappearance. The twisted story she has to tell about the past--and the threat that follows in her wake--will test the bonds of this strong family, and thrust Bodine into a darkness she could never have imagined"--

Saving faith: a novel (Warner, Warner Bks, Warner Books, 1999)
When Faith Lockhart meets to inform the FBI about everything she knows about the powerful lobbyist with whom she has worked who is manipulating the US government policy and who in the process made some very dangerous enemies.

Fast ice: a novel from the Numa files (NUMA, 18,, 2021)
In the early days of World War II, the infamous German Luftwaffe embark upon an expedition to Antarctica, hoping to set up a military base to support their goal of world domination. Though the military outpost never comes to fruition, what the Nazis find on the icy continent indeed proves dangerous...and will have implications far into the future. In the present day, Kurt Austin and his assistant Joe Zavala embark for the freezing edge of the world after a former NUMA colleague disappears in Antarctica. While there, they discover a photo of the Luftwaffe expedition of 1939, and are drawn into a decades-old conspiracy. Even as they confront perilous waters and frigid temperatures, they are also are up against a terrifying man-made weapon--a fast-growing ice that could usher in a new Ice Age. Pitted against a determined madman and a monstrous storm, Kurt and the NUMA team must unravel the Nazi-era plot in order to save the globe from a freeze that would bury it once and for all.

Two good dogs (St. Martin's Press, 2017)
"When Cody, a troubled fourteen-year-old, witnesses a murder, she tells no one. But it begins a spiral for her from which she cannot escape. Her worried mother Skye thinks a change of scene is just what her introverted, withdrawn daughter needs and since her dream has always been to own an inn, she jumps at the chance to buy a dilapidated bed & breakfast in the Berkshires. But being an innkeeper is harder than it seems and Cody still seems to fall in with the wrong crowd. When Adam March arrives as the inn's only guest, he is accompanied by his rescued pit bull, Chance, a dog who has saved Adam in more ways than one. Cody and Chance begin a wary bond and soon, Adam finds another rescue who needs the kind of attention he gave Chance years ago. With Adam and Skye beginning a tentative relationship and Chance showing Cody how to trust again, this new-found family seems to be on the brink of second chances. But soon, a murderer is closing in--someone hiding in plain sight, and threatening everything and everyone--even Cody's life"--

Lethal (Hachette Audio, Grand Central Pub, Grand Central Publishing, 2001)
After Honor Gillette is visited by Lee Coburn, a suspected murderer seeking a valuable object that Honor's late husband left behind, they find themselves running from the FBI and untangling a web of corruption and depravity.

The forgotten (Puller, 2,, 2012)
After he receives a posthumous note from his aunt hinting that things are horribly amiss in her Florida Gulf Coast town, Army Special Agent John Puller uncovers a shocking conspiracy.

Half Moon Bay: a novel (Clay Edison, 3,, 2020)
"Deputy coroner Clay Edison discovers that buried secrets can be deadly in this riveting thriller from a father-son team of bestselling authors who write "brilliant, page-turning fiction" (Stephen King). Deputy Coroner Clay Edison has his hands full. He's got a new baby who won't sleep. He's working the graveyard shift. And he's trying, for once, to mind his own business. Then comes the first call. Workers demolishing a local park have made a haunting discovery: the decades-old skeleton of a child. But whose? And how did it get there? No sooner has Clay begun to investigate than he receives a second call--this one from a local businessman, wondering if the body could belong to his sister. She went missing fifty years ago, the man says. Or at least I think she did. It's a little complicated. And things only get stranger from there. Clay's relentless search for answers will unearth a history of violence and secrets, revolution and betrayal. Because in this town, the past isn't dead. It isn't even past. It's very much alive. And it can kill"--

Just the nicest couple (Park Row Books, Thorndike Press, 2023)
"A husband's disappearance links two couples in this twisty thriller from New York Times bestselling author Mary Kubica Jake Hayes is missing. This much is certain. At first, his wife, Nina, thinks he is blowing off steam at a friend's house after their heated fight the night before. But then a day goes by. Two days. Five. And Jake is still nowhere to be found. Lily Scott, Nina's friend and coworker, thinks she may have been the last to see Jake before he went missing. After Lily confesses everything to her husband, Christian, the two decide that nobody can find out what happened leading up to Jake's disappearance, especially not Nina. But Nina is out there looking for her husband, and she won't stop until the truth is discovered"--

The lucky one (Hachette, Hachette Audio, Grand Central Pub, Grand Central Publishing, 2008)
Coming into the possession of a photograph of a smiling woman he has never met, a man experiences a chain of fortuitous events that causes him to regard the photograph as a lucky charm, a belief that prompts a heartfelt search for the woman.

Untouchable (Cutter Sutter and Salinas, ,, 2019)
"A man's quest to find answers for those who are haunted by the past leads him deeper into the shadows in this electrifying novel from the New York Times bestselling author of Promise Not to Tell. Quinton Zane is back. Jack Lancaster, consultant to the FBI, has always been drawn to the coldest of cold cases, the kind that law enforcement either considers unsolvable or else has chalked up to accidents or suicides. As a survivor of a fire, he finds himself uniquely compelled by arson cases. His almost preternatural ability to get inside the killer's head has garnered him a reputation in some circles--and complicated his personal life. The more cases Jack solves, the closer he slips into the darkness. His only solace is Winter Meadows, a meditation therapist. After particularly grisly cases, Winter can lead Jack back to peace. But as long as Quinton Zane is alive, Jack will not be at peace for long. Having solidified his position as the power behind the throne of his biological family's hedge fund, Zane sets out to get rid of Anson Salinas's foster sons, starting with Jack" --

A minute to midnight (Atlee Pine, 2,, 2019)
'My sister was abducted from here nearly thirty years ago. The person who took her was never found. And neither was she. Her abductor nearly killed me. So I'm back here now trying to find the truth.' Atlee Pine has spent most of her life trying to find out what happened that fateful night in Andersonville, Georgia. Her six-year-old twin sister, Mercy, was taken and Atlee was left for dead while their parents were apparently partying downstairs. One person who continues to haunt her is notorious serial killer, Daniel James Tor, confined to a Colorado maximum security prison. Does he really know what happened to Mercy? The family moved away. The parents divorced. And Atlee chose a career with the FBI dedicating her life to catching those who hurt others. When she oversteps the mark on the arrest of a dangerous criminal, she's given a leave of absence offering the perfect opportunity to return to where it all began, and find some answers. But the trip to Andersonville turns into a roller-coaster ride of murder, long-buried secrets and lies. And a revelation so personal that everything she once believed to be true is fast turning to dust.

Marauder: a novel of the Oregon files (Oregon files, ,, 2020)
"It is up to Juan Cabrillo and the crew of his ship, the Oregon, to stop a terrorist plot to release a deadly chemical weapon across the globe in the explosive new novel in Clive Cussler's #1 New York Times bestselling series"--

Lady in the lake: a novel (William Morrow, William Morrow, an imprint of HarperCollinsPublishers, 2019)
The revered New York Times bestselling author returns with a novel set in 1960s Baltimore that combines modern psychological insights with elements of classic noir, about a middle-aged housewife turned aspiring reporter who pursues the murder of a forgotten young woman. In 1966, Baltimore is a city of secrets that everyone seems to know--everyone, that is, except Madeline "Maddie" Schwartz. Last year, she was a happy, even pampered housewife. This year, she's bolted from her marriage of almost twenty years, determined to make good on her youthful ambitions to live a passionate, meaningful life. Maddie wants to matter, to leave her mark on a swiftly changing world. Drawing on her own secrets, she helps Baltimore police find a murdered girl--assistance that leads to a job at the city's afternoon newspaper, the Star. Working at the newspaper offers Maddie the opportunity to make her name, and she has found just the story to do it: a missing woman whose body was discovered in the fountain of a city park lake. Cleo Sherwood was a young African-American woman who liked to have a good time. No one seems to know or care why she was killed except Maddie--and the dead woman herself. Maddie's going to find the truth about Cleo's life and death. Cleo's ghost, privy to Maddie's poking and prying, wants to be left alone. Maddie's investigation brings her into contact with people that used to be on the periphery of her life--a jewelery store clerk, a waitress, a rising star on the Baltimore Orioles, a patrol cop, a hardened female reporter, a lonely man in a movie theater. But for all her ambition and drive, Maddie often fails to see the people right in front of her. Her inability to look beyond her own needs will lead to tragedy and turmoil for all sorts of people--including the man who shares her bed, a black police officer who cares for Maddie more than she knows.

The girl on the train (Penguin Group Usa, Findaway World, LLC, Penguin Audio, Riverhead Books, Riverhead Books, a member of Penguin Group (USA), 2015)
Obsessively watching a breakfasting couple every day to escape the pain of her losses, Rachel witnesses a shocking event that inextricably entangles her in the lives of strangers.

Ashley Bell: a novel (Bantam Books, Recorded Books, 2015)
"Who is Ashley Bell? From #1 New York Times bestselling author Dean Koontz comes the must-read thriller of the year, perfect for readers of dark psychological suspense and modern classics of mystery and adventure. Brilliantly paced, with an exhilarating heroine and a twisting, ingenious storyline, Ashley Bell is a new milestone in literary suspense from the long-acclaimed master"-- Provided by publisher. "At twenty-two, Bibi Blair's doctors tell her that she's dying. Two days later, she's impossibly cured. Fierce, funny, dauntless, she becomes obsessed with the idea that she was spared because she is meant to save someone else. Someone named Ashley Bell. This proves to be a dangerous idea. Searching for Ashley Bell, ricocheting through a Southern California landscape that proves strange and malevolent in the extreme, Bibi is plunged into a world of crime and conspiracy, following a trail of mysteries that become more sinister and tangled with every twisting turn"-- Provided by publisher.

The warning (Grand Central Pub, Grand Central Publishing, 2019)
Two roads lead to Mount Hope. None leads out. There's no place to run in a community that's been taken and is being intentionally kept off the grid. A small southern town was evacuated after a freak power-plant accident. As the first anniversary of the mishap approaches, some residents are allowed to return past the national guard roadblocks. Mount Hope natives Maggie and Jordan quickly discover that their hometown is not as it was before. Downed cellular networks fail to resume service. Animals savagely attack humans. And the damaged power plant, where Jordan's father is an engineer, is under military lockdown. As friends and family morph into terrifying strangers, the Maggie and Jordan increasingly turn to each other. Their determination to discover who--or what--has taken control of Mount Hope soon has them in the cross-hairs of a presence more sinister than any they could have imagined.